1994
DOI: 10.1007/bf00024796
|View full text |Cite
|
Sign up to set email alerts
|

Cloning an ipt gene from Agrobacterium tumefaciens: characterisation of cytokinins in derivative transgenic plant tissue

Abstract: The isopentenyl transferase gene was isolated from Agrobacterium tumefaciens AcH5 using polymerase chain reaction and transformed into Petunia and Kalanchoe using both A . tumefaciens and A . rhizogenes transformation systems . Morphological evidence and elevated endogenous cytokinin levels indicated that the PCR product was an active gene . Accurate quantification of the cytokinins was obtained by radioimmunoassay, following purification and separation of the free bases and ribosides by HPLC . Of the six cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
8
0
3
Order By: Relevance
“…For construction of the transformation vector, attR recombination sites (Gateway Technology, Invitrogen) were cloned into the vector pMJM (McKenzie et al, 1994), creating pHJMGW. A 4-kb-long cassette from pMJMGW containing the maize (Zea mays) ubiquinone promoter (ubi1) and the attR recombination sites was cloned into pCAMBIA2301.…”
Section: Agrobacterium Tumefaciens Strain and Culture Preparationmentioning
confidence: 99%
“…For construction of the transformation vector, attR recombination sites (Gateway Technology, Invitrogen) were cloned into the vector pMJM (McKenzie et al, 1994), creating pHJMGW. A 4-kb-long cassette from pMJMGW containing the maize (Zea mays) ubiquinone promoter (ubi1) and the attR recombination sites was cloned into pCAMBIA2301.…”
Section: Agrobacterium Tumefaciens Strain and Culture Preparationmentioning
confidence: 99%
“…Two primers were designed that flanked the coding and termination regions of a previously isolated ipt gene sequence (McKenzie et al, 1994). PCR was performed using a Perkin Elmer-Cetus kit according to the manufacturer's instructions.…”
Section: Pcrmentioning
confidence: 99%
“…This gene encodes the enzyme isopentenyl transferase, which catalyzes the rate-limiting step of the cytokinin biosynthetic pathway (Akiyoshi et al, 1984;Barry et al, 1984), in which ⌬ 2 -isopentenyl PPi is condensed with AMP to form isopentenyl AMP. The introduction of the ipt gene into the plant genome results in elevated levels of cytokinin in the transformed tissue (Smigocki and Owens, 1988;Beinsberger et al, 1991;Yusibov et al, 1991;McKenzie et al, 1994), together with associated morphological changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In those transgenic plants, the ipt gene was driven by various promoters, for example constitutive, native, and inducible promoters (Smigocki 1991;Yusibov et al 1991;Rupp et al 1999;van der Graaff et al 2001;Geng et al 2001Geng et al , 2002. Transgenic plants or tissues with ipt expression under the control of a constitutive promoter have been clearly associated with a remarkable increase in cytokinin content; this increase, in turn, resulted in dramatic changes in morphological characteristics, such as non-elongated shoots, bushy phenotypes with a severe lack of apical dominance, small round or serrated leaves, undeveloped roots, delayed leaf senescence, and sterility (Smigocki 1991;Mckonzie et al 1994;Geng et al 2001;van der Graaff et al 2001;Guo et al 2005). Although a number of studies have found that cytokinins have a clear role in plant growth and cell development, it remains to be elucidated how the altered in-vivo hormonal concentrations can vigorously trigger plant development.…”
Section: Introductionmentioning
confidence: 99%